Recycling of solid wastes at kindergartens centres running title; recycling of solid wastes - Radin Mohamed, Radin Maya Saphira; Abduh Algheethi, Adel Ali Saeed; M.A., Yaakob (Prince of Songkla University, 2017)
The present study aimed to conduct an activity on environmental awareness campaign at a kindergarten centre, with the children age 4-6 years old. The activity included identify the various types of waste generated at the kindergarten and to realize the conservation practice by participating in simple waste management strategies and an explanation about recycling, reusing and reducing waste (3R). The activity provided the children more awareness about the importance of minimising the plastic wastes. The activity had created an interesting experience to the young generation through practice activity and has given a light on the nature conservation along their growing years. It can be concluded that the awareness of environmental issues among children have raised up as noted by looking at students physical expression. Children have understand the potential to conserve nature from a simple action which is recycling. After the activity, children’s were able to identify and divide the rubbish.